Otomatisasi Pergerakan Kamera Pada Animasi Sejarah Jayanegara Dan Gapura Bajang Ratu Menggunakan Teknologi Machinima - Irdatul Kamalah (Melek IT : Information Technology Journal, 2019)
The development of animated films is now deepening in the history story. Already many history-history in Indonesia made in the form of animated film, but the manufacture is still in frame by frame. Taking the problem point out of this research will be made a 3D animated film that tells history by utilizing camera automation using machinima technology in order to take shot per-scene automatically and move in real-time as video capture process in real world. In an experiment the camera can shoot and move automatically by utilizing object and trigger games, thus the camera is running as desired.